RANCANG BANGUN APLIKASI KOPERASI SIMPAN PINJAM WIDYAEZA SEJAHTERA BERBASIS WEB DAN MOBILE - Fadilah, Wiya; Hikmah, Nuzul; Misdiyanto, Misdiyanto (Foristek, 2024)
The objectives to be achieved in this study are to design and build mobile and web applications for the widyaeza sejahtera savings and loan cooperative, the research method used is the stages of this research using the UML (Unified Modeling Languange) modeling language. Using UML because it provides visualization of modeling to users of various programming languages, modeling systems with object-oriented concepts (PBO). The results of black box testing research, User Acceptance Testing testing by conducting a survey using a questionnaire. This questionnaire is shown to 30 users, namely cooperative members and the general public, the results of responses from 30 respondents can be calculated as the highest value of 900 and the lowest of 180, so the percentage calculation = 680 / 900 x 100% = 75. 5% of this cooperative application is classified as strong from the user's assessment.